Sedimentology of the Cape Town boulder beds - Akkaş, Tuğçe (University of Cape Town, 2025)
Gravelly sediment layers in fossil beaches around the Cape Peninsula and False Bay in South Africa are assumed to be Pliocene in age and are essential for reconstructing the ancient sedimentary dynamics along the shoreline in the greater Cape Town region. The cobble- to boulder-size clasts in these fossil beaches point to a genesis that can be linked to the erosion of local rocky shores during hurricanes and “super storms”. This mode of formation seems similar to the Pliocene fossil beaches located at different elevations around the world (aka 'the Pliocene sea-level paradox'). Although mapped c. 100 years ago, to date, no modern sedimentological study has been conducted on Cape Town's fossil beaches. Clast characteristics (e.g., clast size, sorting, roundness, composition) of the gravelly layers had been quantified in the field and by the processing of field images using ImageJ software. Our results show that the fossil beaches are dominated by cobble-sized orthoquartzite clasts and display a variety of percussion marks. Originating locally from the Ordovician Peninsula Formation, these clast-supported, rounded clasts decrease in size from east to west, with the maximum clast diameter of >3.2m being recorded at Kogel Bay in False Bay. While this sedimentological study of Cape Town's fossil beaches elucidates the ancient marine dynamics during their genesis, linking them with other Pliocene fossil beaches requires further investigation through their age assessment. Irrespective of their age, the sedimentological properties and stratigraphic position of the fossil beaches above the modern sea level show that during sedimentation not only was the relative sea level higher by up to 30 m, but also that these deposits formed in powerful marine events that are often associated with rising global temperatures.